Pelatihan Membangun Website CRUD Dengan Pemrograman PHP Pada Siswa/I SMK Swasta Free Methodist Medan - Fahmi Ruziq; Subhan Hafiz Nanda Ginting; M. Rhifky Wayahdi (Universitas Muhammadiyah Manado, 2024)
Education has become the primary foundation for the young generation in the digital age. Through dedication to society, a positive contribution to the world of education can be realized. Although IT graduates are on the rise, most are not yet in line with industry standards. The development of soft skills has become crucial in producing successful graduates. Web development remains in demand, however, the gap between education and labour market demand needs to be overcome. This paper deals with